Karakteristik asam amino dan kandidat bakteri probiotik produk fermentasi teritip (Anomia ephippium) di Bangka - Ardiansyah Kurniawan; Khoirul Muslih (Jurusan Akuakultur, Universitas Bangka Belitung, 2014)
Teritip (Anomia ephippium) was well known by local people of Bangka Belitung Island as raw material for traditional fermented product called kecalo teritip. The aims of the study were to identify the content of amino acids and fermenting bacterias of the fermented product as a potential functional food. The steps of production process of the fermented product were the collecting of teritip sample from its substrate on the rocks along the beach, separating the whole edible part from the shells of teritip, and then the flesh were washed and salt-fermented. The amino acids of the fermented product were aspartic acid 2,59%, glutamic acid 3,24%, serine 0,55%, histidine 0,43%, glisine 1,69%, threonine 1,36%, arginine 0,96%, alanine 2,1%, tyrosine 0,37%, methionine 0,83%, valine 1,75%, phenilalanine 1,26%, isoleusine 2,15% dan lysine 1,59%. The identification of bacterias showed that there were five main bacterias in the product e.g Serratia marcescens, Acinetobacter baumannii, Actinobacillus sp., Bacillus cereus, dan Pseudomonas putida. High content of amino acids in the fermented product were suitable to be a functional food.